Pemantapan Keuangan UMKM: Penerapan Sistem Pembukuan Sederhana di Desa Kuning Gading - Yasmir Yasmir; Mela Sari; Tarjo Tarjo (Lembaga Pengembangan Kinerja Dosen, 2026)
Usaha Mikro Kecil Menengah (UMKM) play a strategic role in Indonesia’s economy, serving as key drivers of inclusive economic growth and major contributors to employment creation. Despite their importance, many UMKM operators continue to face significant challenges in financial management, particularly due to the absence of structured and systematic financial record-keeping practices. This condition is also evident among UMKM in Kuning Gading Village, Unit XVIII Kuamang Kuning, where most businesses are still managed in a traditional manner with inadequate bookkeeping systems. This community service program aims to enhance financial literacy and strengthen the capacity of UMKM actors to implement simple bookkeeping as a foundation for effective business financial management. The methods employed include needs assessment through field observation, educational and practical training sessions, hands-on mentoring, and evaluation using pre-test and post-test instruments. The results indicate a significant improvement in participants’ understanding and skills related to transaction recording, separation of business and personal finances, and preparation of simple cash flow statements. Evaluation outcomes show an increase in competency scores from an initial range of 20%–40% to 75%–85% after the training. Furthermore, the program fostered a positive shift in participants’ mindset toward more professional and accountable business management practices. Therefore, the implementation of simple bookkeeping is proven to be an effective initial strategy for strengthening MSME financial governance and supporting sustainable business development at the local level.